Pengaruh amalan pengurusan sumber manusia (PSM) terhadap hasil PSM di IPTS bukan bertaraf universiti - Norasmah Othman,; Zuraidah Ahmad,; Mohd Izham Mohd Hamzah, (Penerbit Universiti Kebangsaan Malaysia, 2010)
The purpose of this study is to examine the link between human resource management (HRM) practices and the outcomes of HRM. HR practices consist of staff selection, training and development, career planning and development, performance appraisal, rewards, safety and health, and workers relation. On the other hand, HRM outcomes include as skills, attitude and behaviour. The research is based on a sample gathered from 23 non-university private higher educational institutions (PHEIs) in the southern region of West Malaysia. This survey used questionnaires as its main instrument and is conducted on 341 respondents for three groups of employees: managers, academicians dan supporting staffs . The stepwise multiple regression analysis shows that 63.5 percent of the changes in attitude is due to its relationship with HRM practices namely workers relation, rewards, staff selection and performance appraisal. Results also provide empirical proofs that attitude mediated the relationship between HR practices and staff behaviour and skills